Administrative legal act and administrative agreement: legal characteristic - Чабан, Валентин Павлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article is devoted to the problem issues of legal characteristics of administrative legal acts and administrative agreements in the public administration activities. The main criteria classification of administrative legal acts are analyzed. Their main features and legal entity are defined. A comparative legal characteristic of administrative legal acts and administrative agreements is done. Based on the analysis of legal literature and practice of public administration the author offers the most meaningful classification of administrative legal acts: 1) by the body that made the act; 2) by the type of act; 3) by time of adoption of the act; 4) by the number of administrative legal act; 5) by alphabetical basis; 6) by subject of regulation. Contractual relationship let individual to make personified expression of approval and mutually beneficial joint decisions. Conclusion administrative agreement gives the benefits which it has in itself and is a call to action for both. Public administration in each case must justify their choice between the two means of influence and decide which is better to use: direct instruction or agreement. Administrative agreement as opposed to direct powerful imperative to take account of and comply interests and subordinate side that some measure is incentive to perform actions in the public interest. Conclusion of the administrative legal agreements as well as publication of administrative acts must be carried in the furrows competence of public administration. This is a prerequisite, which follows from the principle inherent right «all that is not permitted by law is prohibited».